Sugarcane, agro-industrial alternatives - Singh, G. B. (Gajendra B.).; Solomon, S. (New Delhi Oxford & IBH Pub. Co., 1995)
Contributed papers.
Includes bibliographical references and index.
Keywords: Sugar trade -- India; Sugar trade -- India; Sugar manufacture and refinery -- India